ANALYSIS OF THE FINANCIAL PERFORMANCE OF STATE-OWNED ENTERPRISES (BUMN) BANKS BEFORE AND DURING THE COVID-19 PANDEMIC - Panjaitan, Raya; Silaban, Pantas H.; Marbun, Roma Narumata (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
The research objective was to examine and analyze the effect of Job Satisfaction, Work Discipline, and Promotion on Employee Performance at PT. Sumatra Anugerah Teknindo Perkasa Medan. The population in this study was 167 employees and the sample size in this study was 118 employees. The sampling technique used was random sampling. Data collection techniques used questionnaires, interviews and documentation studies. The data analysis technique uses multiple linear regression analysis. The results of testing the hypothesis partially obtained tcount > ttable or 3.428 > 1.981 and significantly obtained 0.001 <0.05, meaning that partially Job Satisfaction has a positive and significant effect on Employee Performance at PT. Sumatra Anugerah Teknindo Perkasa Medan. The value of tcount > ttable or 4, 610 > 1.981 and the significant obtained is 0.000 <0.05, meaning that partially Work Discipline has a positive and significant effect on Employee Performance at PT. Sumatra Anugerah Teknindo Perkasa Medan.